Safety and reactogenicity of the adjuvanted recombinant zoster vaccine: experience from clinical trials and post-marketing surveillance. (November 2021) - Fiore, Joseph; Co-van der Mee, Maribel Miranda; Maldonado, Andrés; Glasser, Lisa; Watson, Phil
An adjuvanted recombinant zoster vaccine (RZV) is licensed for the prevention of herpes zoster. This paper reviews its safety and reactogenicity. A pooled analysis of two pivotal randomized Phase-3 trials (NCT01165177, NCT01165229) in adults ⩾50 years found that more solicited adverse events (AEs) were reported with RZV than placebo. Injection site pain was the most common solicited AE (RZV: 78.0% participants; placebo: 10.9%). Grade-3 pain occurred in 6.4% of RZV and 0.3% of placebo recipients. Myalgia, fatigue, and headache were the most commonly reported general solicited AEs (RZV: 44.7%, 44.5%, and 37.7%, respectively; placebo: 11.7%, 16.5%, and 15.5%, respectively). Most symptoms were mild to moderate in intensity with a median duration of 2–3 days. The intensity of reactogenicity symptoms did not differ substantially after the first and second vaccine doses. The pooled analysis of the pivotal Phase-3 trials did not identify any clinically relevant differences in the overall incidence of serious adverse events (SAEs), fatal AEs or potential immune-mediated diseases (pIMDs) between RZV and placebo. Reactogenicity in five studies of immunocompromised patients ⩾18 years (autologous stem cell transplant, human immunodeficiency virus, solid tumors, hematological malignancies, and renal transplant; NCT01610414, NCT01165203, NCT01798056, NCT01767467, and NCT02058589) was consistent with that observed in the pivotal Phase-3 trials. There were no clinically relevant differences between RZV and placebo in the immunocompromised populations with regard to overall incidence of SAEs, fatal AEs, pIMDs, or AEs related to patients' underlying condition. Post-marketing surveillance found that the most commonly reported AEs were consistent with the reactogenicity profile of the vaccine in clinical trials. Overall, the clinical safety data for RZV are reassuring.